The effects of a premarital program (Evening for Engaged Couples) on self-esteem, communication skills, and interpersonal relationship - Lauw, Jennifer C. (Animo Repository, 1997)
This study determines the effects of a premarital program called Evening for Engaged Couples on self-esteem, communication skills, and interpersonal relationship. The Coopersmith Self-Esteem Inventory, Premarital Communication Inventory, and Fundamental Interpersonal Relationship Orientation - Behavior were utilized to measure the levels of self-esteem, communication skills, and interpersonal relationship, respectively. These inventories were administered to experimental and control couples as pre- and posttests. There were seven couples in experimental and seven couples in control groups. The t-test was utilized to test the hypotheses. The results of the study showed that the experimental couples experienced significant improvement in the communication skills, t(13) = 6.39, p .05, and interpersonal relationship as a whole, T(13) .05, and interpersonal relationship in the area of control, t(13) = 0.34, p .05.Gain scores showed a significant increase by the experimental couples in communication skills, t(26) = 6.50, p .05, and interpersonal relationship in the areas of inclusion, t(26) .05, and interpersonal relationship as a whole, t(26) = 1.64, p .05, and in the area of control, t(26) = 0.38, p .05. The results confirmed the hypotheses that the premarital program Evening for Engaged Couples has significant effects on the communication skills of premarital couples and interpersonal relationship in the areas of inclusion and affection. However, the program has no significant effects on self-esteem and interpersonal relationship as a whole and in the area of control. Further studies are recommended to determine the long-term effects of the program and comparison of effects of various premarital programs.